Produkty rolnictwa ekologicznego w opinii konsumentów - Łuczka-Bakuła, Władysława (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The consumers' opinion on the features, motives of purchase, confidence, and intention of organic food consumption increase in the future were discussed in this article. It was found that the inquired positively perceive organic products in regard to their prohealth features. The features attributed to organics, as well as motives of purchase indicate that. On the contrary, the environmental aspects have less meaning. It proves lower environmental awareness of Polish consumers in comparison to other countries, in which the distinguishing feature of this market segment is connecting the purchase and consumption of organic food with the environmental impact. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 288-295